Tomorrow's geography for Edexcel GCSE specification A - Warren, Steph; Harcourt, Mike (Hodder Education, 2012)
Endorsed by Edexcel, this fourth edition of the best-selling title is designed to prepare your students for exam success for the latest Edexcel A specification. It covers all four units of the specification, including comprehensive coverage of Unit 1 Geographical Skills and Challenges for the Planet, all the content for Units 2 and 3, and Controlled Assessment for Unit 4. This edition reinforces students' key geographical skills of map-work, decision making and interpretation of data with a range of differentiated activities, gives plenty of exam practice with sample examination questions and engages your students with case studies using real-life examples from local, regional and national levels. It features a map of the world with countries mentioned in the book highlighted so there is no need for a separate atlas. Map symbols are also included for easy reference."